2018
DOI: 10.1093/jn/nxy223
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Purine Metabolites Are Elevated in Fluids from Adults and Infants and in Livers from Mice Fed Diets Depleted of Bovine Milk Exosomes and their RNA Cargos

Abstract: Background Humans and mice absorb bovine milk exosomes and their RNA cargos. Objectives The objectives of this study were to determine whether milk exosome– and RNA-depleted (ERD) and exosome- and RNA-sufficient (ERS) diets alter the concentrations of purine metabolites in mouse livers, and to determine whether diets depleted of bovine milk alter the plasma concentration and urine excretion of purine metabolites in adults and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Similarly, the concentration of urinary purine metabolites was significantly higher in infants fed with soy milk or formula than breast-fed infants. This difference suggested that the absence of breast milk-derived exosomes could affect normal brain function in infants (Aguilar-Lozano et al, 2018). A longitudinal study indicated that psychomotor development is higher in breastfeeding babies than in babies fed with formula milk or soy milk.…”
Section: Milk-derived Evs and Neural Developmentmentioning
confidence: 99%
“…Similarly, the concentration of urinary purine metabolites was significantly higher in infants fed with soy milk or formula than breast-fed infants. This difference suggested that the absence of breast milk-derived exosomes could affect normal brain function in infants (Aguilar-Lozano et al, 2018). A longitudinal study indicated that psychomotor development is higher in breastfeeding babies than in babies fed with formula milk or soy milk.…”
Section: Milk-derived Evs and Neural Developmentmentioning
confidence: 99%
“…Aberrant metabolism of purines has been implicated in the loss of SLM in mice fed the ERD diet. The purine metabolites adenosine and ATP play an important role in SLM, and hepatic levels of purine metabolites were substantially higher in mice fed the ERD diet compared with ERS controls (138,139). Effects of milk feeding on purine metabolites were similar in human cohorts compared with the changes observed in mice: The concentrations of purine metabolites were higher in plasma and urine in human milk avoiders compared with milk consumers and in infants fed soy formula compared with infants fed human milk or milk formula (139).…”
Section: Phenotypes Of Dietary Depletion Of Exosomes and Cargosmentioning
confidence: 99%
“…The purine metabolites adenosine and ATP play an important role in SLM, and hepatic levels of purine metabolites were substantially higher in mice fed the ERD diet compared with ERS controls (138,139). Effects of milk feeding on purine metabolites were similar in human cohorts compared with the changes observed in mice: The concentrations of purine metabolites were higher in plasma and urine in human milk avoiders compared with milk consumers and in infants fed soy formula compared with infants fed human milk or milk formula (139). The mechanisms by which milk exosomes and RNA cargos alter purine metabolism is unknown, although the authors proposed that miR-362-3p and miR-30a-5p in milk exosomes might be responsible for the differential expression of 5 × -nucleotidase, cytosolic IIIB, and adenosine deaminase in livers from mice fed ERD or ERS diets.…”
Section: Phenotypes Of Dietary Depletion Of Exosomes and Cargosmentioning
confidence: 99%
“…Milk EVs are released by the luminal epithelium and have been demonstrated to survive digestion in vitro and may be taken up by recipient cells in the infant 6 10 . These milk EVs can then induce changes in gene expression in vitro 6 , induce systemic metabolic alterations in vivo 9 , and may play a role in newborn immunity 11 13 .…”
Section: Introductionmentioning
confidence: 99%